2014
DOI: 10.3174/ajnr.a3953
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Infarct Volume and Intracranial Hemorrhage Associated with Intra-Arterial Nonionic Iso-Osmolar Contrast Material in an MCA Occlusion/Reperfusion Model

Abstract: BACKGROUND AND PURPOSE:Infarct volume and intracranial hemorrhage after reperfusion with nonionic low-osmolar and isoosmolar iodinated IRCM has not been previously compared. We postulated that iso-osmolar and low-osmolar iodinated contrast media exert varied effects on cerebral infarct after intra-arterial injection. We compared infarct volume and hemorrhagic changes following intra-arterial infusion of iodixanol, iopamidol, or normal saline in a rat MCA occlusion/reperfusion model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 47 publications
(46 reference statements)
0
11
0
Order By: Relevance
“…SI was measured using similar sequences at both magnets, as follow: Spin-echo . The sequences were tailored to match a concomitant experiment of ICM infusion in a rat model of temporary ischemia performed on the same 3T magnet [8] . SI of each aliquot was measured and normalized to saline (SI contrast/SI saline).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…SI was measured using similar sequences at both magnets, as follow: Spin-echo . The sequences were tailored to match a concomitant experiment of ICM infusion in a rat model of temporary ischemia performed on the same 3T magnet [8] . SI of each aliquot was measured and normalized to saline (SI contrast/SI saline).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, we did not compare side-by-side signal changes of blood and ICM (T1 and T2 relaxation times for blood are well known in the literature - Table 1). One potential limitation is that our T1-WI sequence was similar in both 1.5T and 3T magnets, with an optimized TR for high magnetic fields [8] . Even though this could lead to changes in SI not usually seen at 1.5T, we believe the characterization on T2-WI was significantly more conspicuous, particularly with iopamidol.…”
Section: A B C Dmentioning
confidence: 99%
See 1 more Smart Citation
“…2 It is reasonable to further hypothesize, then, that nonionic iso-osmolal IRCM may have a less harmful net effect in the setting of acute stroke than nonionic LOCM. No comparative data in IV or IA IRCM use in human stroke are available to refute that hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…1 Iso-osmolal iodixanol (290 mOsm/kg H 2 O) infusion led to smaller infarcts and less ICH compared with both low-osmolal iopamidol and saline in a similar model. 2 Dzialowski et al 3 reported reduced odds of favorable outcome in patients receiving intravenous IRCM for CT angiography before IV thrombolysis.…”
mentioning
confidence: 99%